2009
DOI: 10.1007/s00436-009-1429-6
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal and repellent activities of thymol from the essential oil of Trachyspermum ammi (Linn) Sprague seeds against Anopheles stephensi

Abstract: Essential oil of seeds of Trachyspermum ammi (Linn.) Sprauge and its pure constituent thymol showed promising results when evaluated for larvicidal, oviposition-deterrent, vapor toxicity, and repellent activity against malarial vector, Anopheles stephensi. Thymol was 1.6-fold more toxic than the oil toward fourth-instar larvae of A. stephensi with LD(50) values of 48.88 and 80.77 microg/ml, respectively. Egg laying by female adults of A. stephensi was much significantly reduced when exposed to vapors of thymol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(52 citation statements)
references
References 25 publications
(24 reference statements)
4
44
0
1
Order By: Relevance
“…The results clearly show that repellent activity was dose dependent. This repellent activity is comparable to previously reported at the dose of 25.0 mg/mat, thymol provided complete repellency, whereas Trachyspermum ammi seed oil could achieve a repellency of 45.0% and the repellent doses (RD50) observed were 25.02 and 11.63 mg/mat for Trachyspermum ammi seed oil and thymol, respectively against Anopheles stephensi adults (Pandey et al, 2009). Amer and Mehlhorn (2006) have reported that the five most effective oils were those of Litsea (Litsea cubeba), Cajeput (Melaleuca leucadendron), Niaouli (Melaleuca quinquenervia), Violet (Viola odorata), and Catnip (Nepeta cataria), which induced a protection time of 8 h at the maximum and a 100% repellency against Aedes aegypti, Anopheles stephensi, and Culex quinquefasciatus.…”
Section: Resultssupporting
confidence: 90%
“…The results clearly show that repellent activity was dose dependent. This repellent activity is comparable to previously reported at the dose of 25.0 mg/mat, thymol provided complete repellency, whereas Trachyspermum ammi seed oil could achieve a repellency of 45.0% and the repellent doses (RD50) observed were 25.02 and 11.63 mg/mat for Trachyspermum ammi seed oil and thymol, respectively against Anopheles stephensi adults (Pandey et al, 2009). Amer and Mehlhorn (2006) have reported that the five most effective oils were those of Litsea (Litsea cubeba), Cajeput (Melaleuca leucadendron), Niaouli (Melaleuca quinquenervia), Violet (Viola odorata), and Catnip (Nepeta cataria), which induced a protection time of 8 h at the maximum and a 100% repellency against Aedes aegypti, Anopheles stephensi, and Culex quinquefasciatus.…”
Section: Resultssupporting
confidence: 90%
“…Previous studies have evaluated the potential use of plants such as C. obtusifolia [13], Trachyspermunammi [14] against An. stephensi, Piper longum and Piper nigrum [15,16], Cassia fistula [17], Coriandrum sativum [18] against Ae.…”
Section: Introductionmentioning
confidence: 99%
“…Essential oil is obtained from the leaves and seeds (Petropoulos et al 2004). Parsley is known as an aromatic, spice as well as herb used for flavoring food (Pandey et al 2009). …”
Section: Introductionmentioning
confidence: 99%